The Effect of Net Profit Margin (NPM), Return On Equity (ROE) and Earning Per Share (EPS) on Stock Prices in Food and Beverage Sub- Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2016-2021 Period - Abdul Aziz; Purnamawati Purnamawati (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
This study has an objective to determine the effect of Net Profit Margin, Return On Equity and Earning Per Share either partially or simultaneously on stock prices in food and beverage companies listed on the Indonesia Stock Exchange for the 2016-2021 period. This study is conducted using quantitative method with secondary data obtained from the Indonesia Stock Exchange. The population in this study are 39 food and beverage companies listed on the Indonesia Stock Exchange for the 2016-2021 period. The sample in this study are 11 food and beverage companies that have been determined using a purposive sampling technique. The data analysis technique used is multiple linear regression analysis. Based on the results of data analysis from the t statistical test or partially, the Net Profit Margin (NPM) variable has a positive and significant effect on stock prices with a coefficient value of 8.401 and a significance level of 0.000 0.05, Return On Equity (ROE) has a positive and insignificant effect on stock prices with a coefficient value of 1.275 and a significance level of 0.207 0.05. Earning Per Share (EPS) has a positive and significant effect on stock prices with a coefficient value of 7.876 and a significance level of 0.000 0.05. Meanwhile, simultaneously, the results of data analysis from the f statistical test show the value of Fcount of 54.966 with the obtained probability value is smaller than alpha, which is 0.000 0.05. Thus, it can be concluded that Net Profit Margin, Return On Equity and Earning Per Share simultaneously have a positive and significant effect on company value. Moreover, the coefficient of determination (R2) obtained in this study is 0.727 or 72.7%.